2019
DOI: 10.1093/ndt/gfz168
|View full text |Cite
|
Sign up to set email alerts
|

Urinary chemokine C-X-C motif ligand 16 and endostatin as predictors of tubulointerstitial fibrosis in patients with advanced diabetic kidney disease

Abstract: Background Interstitial fibrosis and tubular atrophy (IFTA) is a well-recognized risk factor for poor renal outcome in patients with diabetic kidney disease (DKD). However, a noninvasive biomarker for IFTA is currently lacking. The purpose of this study was to identify urinary markers of IFTA and to determine their clinical relevance as predictors of renal prognosis. Methods Seventy patients with biopsy-proven isolated DKD we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…Another chemokine named CXCL16, a scavenger receptor for oxidized low-density lipoprotein (LDL), was reported by Lin et al to be independently associated with a change in renal function in all-stage CKD [ 113 ]. Additionally, it appears to be a marker of renal injury in patients with type 2 DM, where it is independently predictive of microalbuminuria [ 114 , 115 ] and its urinary levels could reflect the degree of interstitial fibrosis and tubular atrophy in patients with advanced diabetic kidney disease [ 116 ]. It appears to also play a role in the etiopathogenesis of preeclampsia, where its blockade could pave the way to the discovery of new treatments of preeclampsia [ 117 ].…”
Section: Chemokinesmentioning
confidence: 99%
“…Another chemokine named CXCL16, a scavenger receptor for oxidized low-density lipoprotein (LDL), was reported by Lin et al to be independently associated with a change in renal function in all-stage CKD [ 113 ]. Additionally, it appears to be a marker of renal injury in patients with type 2 DM, where it is independently predictive of microalbuminuria [ 114 , 115 ] and its urinary levels could reflect the degree of interstitial fibrosis and tubular atrophy in patients with advanced diabetic kidney disease [ 116 ]. It appears to also play a role in the etiopathogenesis of preeclampsia, where its blockade could pave the way to the discovery of new treatments of preeclampsia [ 117 ].…”
Section: Chemokinesmentioning
confidence: 99%
“…In patients with type 2 diabetes enrolled in the ROADMAP (Randomized Olmesartan and Diabetes Micro-Albuminuria Prevention) and observational follow-up studies, enhanced plasma CXCL16 levels, angiopoietin-2, and TGF-β1 were shown to be independently predictive of microalbuminuria [88]. Urinary CXCL16 and endostatin can reflect the degree of interstitial fibrosis and tubular atrophy, which is a risk factor for poor renal outcome in DN patients, and act as biomarkers among these patients [89].…”
Section: Members Of Chemokine CXC Family In Diabetic Nephropathymentioning
confidence: 99%
“…Multiple plasma inflammatory markers were simultaneously measured by multiplex enzyme-linked immunosorbent assay as previously described [32]. We reviewed the previous literature and selected the following candidate inflammatory markers: a proliferation-inducing ligand (APRIL), B-cell activating factor (BAFF), CXCL16, endocan, endostatin, follistatin, IL-6, IL-25, IL-18, monocyte chemoattractant protein-1 (MCP-1), MCP-2, MCP-4, matrix metalloproteinase-7 (MMP-7), MMP-8, osteoprotegerin, PCSK9, receptor activator of nuclear factor-κΒ ligand (RANKL), and tumor necrosis factor-α (TNF-α).…”
Section: Measurement Of Plasma Inflammatory Markersmentioning
confidence: 99%